Mechanistic switch in corrosion behavior of magnesium alloy diamond lattice structures induced by argon plasma treatment - Viviana M. Posada; Alexandru Marin; Tonny Naranjo; Juan Ramírez; Patricia Fernández-Morales (Journal of Magnesium and Alloys)
Advancing 3D magnesium (Mg) development beyond current limitations requires controlling Mg alloy degradation in pre-designed, low-dimension architectures. This study reveals a mechanistic switch in the corrosion behavior of Mg alloy (3.6% Al, 0.8% Zn) diamond lattice structures, induced by plasma nanosynthesis (400 eV Ar+ ions, fluence 1 × 1017 ions/cm2). Plasma treatment of the Mg alloy increases surface Mg from 1.5% to 14.5%, enhances carbonate formation, and generates a nanostructured surface with a Mg carbonate layer over an oxide/hydroxide layer. In vitro and in vivo analyses over 8 wk demonstrate how this treatment fundamentally alters the degradation process and stability of these 3D architectures.While untreated samples initially formed a protective film that subsequently diminished, DPNS-treated samples demonstrated an inverse corrosion behavior. X-ray photoelectron spectroscopy (XPS) and electrochemical impedance spectroscopy (EIS) confirmed the presence of a stable, protective layer composed of magnesium oxide, magnesium hydroxide, and magnesium carbonate on the DPNS-treated surfaces. After 14 days, the DPNS-treated sample exhibited a more positive corrosion potential (-0.69 V versus -1.36 V) and a marginally lower current density (0.73 mA/cm² compared to 0.75 mA/cm²) relative to the control. This protective layer, combined with modified surface topology, initiated a core-to-periphery degradation pattern that maintained structural integrity for up to 8 wk post-implantation. These findings support the conclusion that the DPNS-treated scaffold demonstrates sustained improved corrosion resistance over time compared to the untreated control.Micro-CT revealed plasma-treated samples retained larger struts (504.9 ± 95.3 µm at 8 wk) and formed larger H2 pockets extending 14.2 mm from the implant center, versus 4.9 mm in controls. This corrosion behavior switch enhances stability but risks pore clogging, offering insights for tailoring Mg alloy degradation and H2 evolution in 3D architectures for biomedical applications.